The Art and Science of Cardiac Physical Examination With Heart Sounds and Pulse Wave Forms on CD - Ranganathan, Narasimhan; Sivaciyan, Vahe.; Saksena, Franklin B.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2007)
Despite the fact that more than half the patients seeking care from an internal medicine specialist or a family physician will have either a primary or secondary cardiac problem, the teaching of cardiac auscultation, the physical examination of the heart, has been deteriorating since the advent of such modern diagnostic tools as 2D echocardiology and nuclear imaging. In The Art and Science of Cardiac Physical Examination veteran academic clinicians bring the art and science of cardiac physical examination to the bedside with a tour de force tutorial on techniques needed to elicit various physical signs and to interpret them in relation to the patient's symptoms and underlying cardiac condition. Drawing on twenty-five years of teaching and training physicians and physicians-to-be, the authors integrate the physiology, pathophysiology, and mechanisms behind the various physical signs with a thorough and easy-to-use practical approach that makes a physician feel more comfortable and competent performing the cardiac physical examination. The authors pay particular attention to the interpretation of the jugular venous pulsations and contour and make the physiology and pathophysiology of the normal and abnormal arterial pulse interesting and relevant. They also clarify the apical impulse and its importance. Local and systemic manifestations relevant to cardiac diagnosis are also emphasized and illustrated.  Comprehensive and instructive, The Art and Science of Cardiac Physical Examination provides the student of cardiology with the proper techniques and understanding of the art and science of the cardiac physical examination to develop the skills required of any astute clinician.
Approach to the Physical Examination of the Cardiac Patient -- Arterial Pulse -- Blood Pressure and Its Measurement -- Jugular Venous Pulse -- Precordial Pulsations -- Heart Sounds -- Heart Murmurs -- Heart Murmurs -- Elements of Auscultation -- Pathophysiological Basis of Symptoms and Signs in Cardiac Disease -- Local and Systemic Manifestations of Cardiovascular Disease.
Keywords: Cardiology; Cardiology